Dinâmica de Atrazina em solos de cerrado sob aplicação de biochar - Morais, Leidimar Alves de (2017)
New management practices aimed at the conscious use of production technologies that do not harm the environment are of fundamental importance for agricultural cultivation. Several articles report Biochar potential to mitigate the effects of soil and water contamination by agricultural pesticides in order to contribute to environmental preservation. However, there is still much to elucidate about the interaction of biochar on the dynamics of herbicides in soil. The objective of this work was to investigate the effect of biochar on the Red-Yellow Latosol (Experiment I) and the Plintosol (Experiment II) with different concentrations of biochar after nine and seven years of application. The experiments were conducted to field in Nova Xavantina-MT, where they were installed in a randomized complete block design, composed by the combination of basal fertilization levels (NPK) and biochar doses, both with four replications. The experiment I, installed in 2006, had the application of 0 and 400 kg ha-1 of the formula 00-20-20 of the NPK fertilizer and three doses of biochar (0, 8 and 16 Mg ha-1 ). In experiment II, installed in 2008, 0 and 300 kg ha-1 of NPK fertilizer of formula 05-25-15 and three doses of biochar (0, 16 and 32 Mg ha-1 ) were applied. For the evaluation of the absorption and desorption of atrazine the Batch Balance method was used. The Freundlich isotherm proved to be suitable for describing atrazine adsorption and desorption in both experiments. The application of biochar increased the sorption and reduced atrazine desorption in the two studied soils. This effect is attributed to the contribution of biochar to the total organic carbon content and to the carbon content present in the humina fraction of organic matter in the soil. The results show that the long-term application of biochar has proved to be a suitable management practice in reducing the leaching of atrazine in agricultural soils.